Theoretical-methodological basis of formation social policy of state - I. N. Primyshev (Омский научный вестник: Серия "Общество. История. Современность")
In this article, the author considers the theoretical and methodological basis for the formation and development of social policy in order to clarify its role and place in improving the standard and quality of life of the population. The main objectives of social policy have been studied and systematized. The main directions of the developed programs for the implementation of social policy have been identified. Social policy actors have been identified and investigated and structured. Methodological principles of social policy are summarized. The conclusion notes that social policy is one of the most important areas of activity of the State to increase the effectiveness of the social system, the main task of which is to ensure the necessary standard of living of citizens